Learning Activities by Instilling Religious Values with Karimah Morals at Taam Daarul Muntaz and TPQ Daarul Muntaz - Aziiz, Abdul; Surya, Alviano; Erika, Aprilia Chandra; Hilmawan, Aris; Andriyani, Lusi (Educationist: Journal of Educational and Cultural Studies, 2023)
The level of education is considered very important for each individual, this also applies to early age children because at that age is the golden age, which is seen from the child's sensitivity to what he feels. In this golden age, children start to find out what makes them curious. They start to be enthusiastic about learning to read and find interesting new things. The more interesting he finds at that time, the more opportunities for the child to find a passion or potential that he can develop from an early age. As is known, the level of education available for early childhood is quite diverse, such as TK (kindergarten), TAAM (Muslim children's nursery), TPQ (al-quran education park), PAUD (early childhood education). This level of education is given in order to be able to show a new world to children, help children develop, form good characters for children, increase enthusiasm for learning, and build quality human resources in the future. This is directly related to KKN activities that were made related to the implementation of work programs held at Taam Daarul Muntaz and TPQ Daarul Muntaz. the implementation of the KKN program is balanced and starts from the planning, implementation and final evaluation of the program. KKN group scale program 43 Educational outcomes include the educational value contained in children's learning activities by raising children's enthusiasm for learning and the value of children's creativity through greetings and humor points.